1987
DOI: 10.1016/0014-5793(87)80468-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunoaffinity‐purified opiate receptor specifically binds the δ‐class opiate receptor ligand, cis‐(+)‐3‐methylfentanylisothiocyanate, SUPERFIT

Abstract: Using an antibody generated against the opiate receptor on NG108‐15 cells, we recently purified the putative receptor from this hybrid cell line. We herein report that the purified receptor complex specifically binds tritiated cis‐(+)‐3‐methylfentanylisothiocyanate (SUPERFIT), with the predominant binding associated with a 58 kDa polypeptide chain. Consistent with these findings is the in situ labeling of a 58 kDa protein with [3H]SUPERFIT on NG108‐15 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
8
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 22 publications
4
8
0
Order By: Relevance
“…By comparison, immunocyte opioid receptors purified by affinity chromatography and subsequently analyzed by PAGE have a similar molecular weight to what has previously been reported for 8-class [4,5] and p-class [3,21 ] opioid receptors of neuroendocrine tissue. In addition, the molecular weight of the immunoaffinity-purified immunocyte receptor is consistent with the results of previous in situ labeling experiments of the 8-class opioid receptor on cells of the immune system [18], Moreover, the present study using purified mouse brain recep tors would indicate a similar structural profile to immune cell receptors.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…By comparison, immunocyte opioid receptors purified by affinity chromatography and subsequently analyzed by PAGE have a similar molecular weight to what has previously been reported for 8-class [4,5] and p-class [3,21 ] opioid receptors of neuroendocrine tissue. In addition, the molecular weight of the immunoaffinity-purified immunocyte receptor is consistent with the results of previous in situ labeling experiments of the 8-class opioid receptor on cells of the immune system [18], Moreover, the present study using purified mouse brain recep tors would indicate a similar structural profile to immune cell receptors.…”
Section: Discussionmentioning
confidence: 66%
“…Previous results also suggest that the 8-and u-class opioid receptors have similar if not identical molecular weights [3,5,21], Thus, the present studies were carried out in order to further address whether the binding sites are in close enough proximity to modulate ligand-binding capabilities of one another. Studies of brain opioid receptor structure using the site-directed p-(BIT) and 8-(SUPERFIT) class-specific reagents in in situ labeling techniques revealed that BIT (10-20 uA fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, it was determined upon purification and SDS-polyacrylamide gel electro phoresis that the leukocyte opioid receptor was com posed of four polypeptide chains with Mr of 70,000, 56,000, 46,000 and 31,000 daltons [22], In order to fur ther investigate the physicochemical properties of the receptor, we addressed the functionality of the receptor from NG108-15 cells and leukocytes by determining if purified material could specifically bind an opiate ligand and which chain (or chains) was (were) responsible for its recognition. In studies using cis-(+)-3-methylfentanylisothiocyanate (SUPERFIT), a delta-class-specific opiate receptor ligand, immunoaffinity-purified receptor from NG108-15 and leukocytes specifically recognized SUPERFIT and the 56-to 58-dalton polypeptide chain was associated with all of ihe binding [23].…”
Section: Opiate Receptormentioning
confidence: 99%